DEVELOPING HUMAN CAPITAL AND PROMOTING CREATIVE SKILLS: A GLOBAL EXPERIENCE ANALYSIS (Marketing Journal, 2025)
This article comprehensively studies the issues of human capital development and stimulation of creative abilities. The study analyzes innovative approaches used in different countries of the world, their performance indicators and practical results. Based on a questionnaire, statistical data and case studies, the aspects of human capital development related to creativity are revealed. Experiences in developed and developing countries are compared and effective mechanisms that can be applied in the conditio ns of Uzbekistan are proposed. Based on the results of the study, 430 recommendations for the development of human capital and stimulation of creativity are developed.
Keywords: human capital; creativity; innovative potential; competitiveness; education system; economic growth; intellectual resources